Book Review. A New Contribution to the Treasury of Translation Theory: Encyclopedia of Translation Studies. (2020). O. Kalnychenko & L. Chernovaty, (Eds.). Vol. 2. - Andrienko, Tetiana; Shpeniuk , Iryna (East European Journal of Psycholinguistics, 2021)
Енциклопедія перекладознавства : у 4 т. Т. 2 : пер. з англ. / за ред.: Іва Ґамб’є та Люка ван Дорслара ; за заг. ред.: О. А. Кальниченка та Л. М. Черноватого. Вінниця : Нова Книга, 2020. 280 с. (UTTU Series). ISBN 978-966-382-844-2 Encyclopedia of Translation Studies. (2020). O. Kalnychenko & L. Chernovaty, (Eds.). Translated from English. Volume 2. Vinnytsia: Nova Knyha Publishers. 280 p. As a new contribution to the treasury of translation theory, Nova Knyha Publishers has presented the second volume in a series of the most influential and cutting-edge publications on translation theory and practice in Ukrainian translation. The second volume of Translation Encyclopedia edited by Oleksandr Kalnychenko and Leonid Chernovaty continues to introduce a variety of topics related to translation and translation studies. The publication that has aroused genuine interest of academics and practitioners all over the world is now available to the Ukrainian readers in their native language. It comprises a translation of 35 articles from The Handbook of Translation Studies (edited by Yves Gambier, Luc van Doorslaer, John Benjamins Publishing Company, 2011). The collection includes papers of such prominent translation theorists as Hélène Buzelin, Sherry Simon, Jeroen Vandaele, Dilek Dizdar, Barbara Moser-Mercer, Kaisa Koskinen, Sharon O’Brien, Sonia Colina, Cristina Marinetti, Kirsten Malmkjær, Vicent Montalt, James St. André, Peter Flynn and Yves Gambier, Albert Branchadell, Nike K. Pokorn, Barbara Ahrens, Outi Paloposki, Şehnaz Tahir Gürçağlar, Francis Jones, Cristina Valdés, Andrew Chesterman, Luc van Doorslaer, Reine Meylaerts, Cees Koster, Rachele Antonini, Gideon Toury, Carol O’Sullivan, Brian Mossop, Ritva Leppihalme, David Katan, Cecilia Wadensjö, Jean Boase-Beier, Christina Schäffner, Paul Bandia, Dirk Delabastita. Notably, the collection follows a good tradition of presenting well-known names along with the new authors of breakthrough ideas and original approaches. The book covers a wide range of theoretical issues in the field of translation. New visions and discussions of established theoretical approaches call the readers’ attention to the paradigmatic shifts that have occurred in linguistics in the recent decades – from language-focused to communication-focused and, further, human-focused translation studies. In particular, in Linguistics and translation,Kirsten Malmkjær discusses the relationship between linguistics and translation as well as linguistic theories of translation suggested by J-P. Vinay and J. Darbelnet, J.C. Catford, E-A. Gutt. Hélène Buzelin considers translation from the viewpoint of the agent in Agents of translation, where the concept of “agents” is discussed in relation to socio-historiographic, sociological and ethnographic paths. In Comparative approaches to translation, the author critically evaluates several existing theoretical methods of the comparative procedure, particularly those of Toury, Van Leuven-Zwart, Holmes. A sphere of special interest is comprised by field-specific translation research works. Aspects of different types of oral and written translation such as remote interpreting, institutional, medical, advertising, literary translation are also examined in the collection. In Institutional translation by Kaisa Koskinen, the “institutional translation” refers to activities or translated works within the various concrete institutions that modern societies have built to carry out their governance and control needs. The author also considers genre characteristics of institutional translation, making a valuable contribution to the sociology of translation. This unity of translation theory and practice is a distinctive and valuable trait of the reviewed research collection. Dirk Delabastita in Literary translation defines this type of translation and touches on some issues and aspects of sociolinguistics, history of literary translation. Medical translation and its genres are discussed in Medical translation and interpreting by Vicent Montalt. The nature of poetic text makes it challenging to translate, which has caused much debate about how these challenges should be tackled. Francis R. Jones in Poetry translation describes these issues, as well as the skills, working processes and professional conditions involved in translating poetry. Enriching the general translation theory, these works elaborate on the aspects that comprise translation problems encountered by practitioners. Much attention is devoted to discussion of practical issues encountered in translation. Of great interest to the audience will be the article Realia by Ritva Leppihalme. This paper explains the concept of realia, gives a classification and presents translation strategies of realia with authentic examples representing a number of language pairs. One of the most extensively researched problem in translation studies is the translation of wordplay and Jeroen Vandaele in Wordplay in translation makes his contribution to the scope of these studies. Besides recommendations for practitioners, such works outline new methods of analysis and prompt further insights into translation problems rooted in the differences of cognitive level – worldviews, cultural attitudes, interpretational frames. Undoubtedly the publication will stir the research interest and creative imagination of the young scholars working in the field of translation studies. The publication of the invaluable Handbook in Ukrainian is phenomenal in an array of senses: it opens the access to the research works to a broader Ukrainian-reading audience, involving the scholars and translators of other-than-English languages in discussions; it develops the Ukrainian translation terminology and respective theoretical/cognitive basis; it comprises exemplary translations which may by themselves become the subject of study, comparison and discussion. The publication of the second volume of Translation Encyclopedia (Ed. O. Kalnychenko and L. Chernovaty) cannot be overestimated: it marks a new milestone in the development of the theory and practice of translation. The book will be useful not only to students and scholars in the field of translation studies but also to translation practitioners and researchers working in other subject fields and all who are interested in translation and interpreting. It is sure to raise the discussions of translation problems and difficulties to a new theoretical and practical level. Looking forward to new volumes of the Translation Encyclopedia in Ukrainian, we hail this publication as a remarkable and outstanding event in the history of Ukrainian translation.